Modern Logistics in Tourism and Hospitality Sector: An Analysis based on 21st Century - Shahparan, Mohammad (Journal of Tourism Sustainability, 2024)
Logistics processes and technologies cover many areas like production, economic activities, and the tourism and hospitality sectors. Logistics in the tourism and hospitality sector is essential to tourists’ loyalty, providing excellent tourist service. In hospitality, modern logistics are used to fulfill food, fixtures, furniture and equipment, operating supplies, building materials, entwinement equipment, etc. Modern logistics in the tourism sector help improve the experience and satisfaction of customers, workers, business people, and suppliers. This paper describes the modern logistics in tourism and hospitality based on the 4.0 era. Data was collected from different online sources related to logistics tourism and logistics hospitality, such as Streamline Journal. This research paper connects logistics activities to the tourism and hospitality sector. This paper allows future researchers to connect logistics among the tourism and hospitality sectors easily.